2020
DOI: 10.1101/2020.09.20.20198192
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Panbio antigen rapid test is reliable to diagnose SARS-CoV-2 infection in the first 7 days after the onset of symptoms

Abstract: Background: Real-time reverse transcription polymerase chain reaction (RT-qPCR) is the current recommended laboratory method to diagnose SARS-CoV-2 acute infection, several factors such as requirement of special equipment, time consuming, high cost and skilled staff limit the use of these time-consuming molecular techniques. A more rapid and high-throughput method is in growing demand Methods: Evaluate the performances of the Panbio COVID-19 AG Rapid Test Device (Nasopharyngeal), a rapid immunochromatographic … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
76
1
4

Year Published

2021
2021
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(94 citation statements)
references
References 9 publications
13
76
1
4
Order By: Relevance
“…3 Of the studies that examined positivity rate based on symptom duration, one study found no difference in positivity rate with duration of symptom onset 3 , whereas another found higher sensitivity in individuals with symptom onset < 7 days (sensitivity 86.5%) compared to individuals with symptom onset ≥ 7 days (sensitivity 53.8%). 4 We found no difference in Panbio sensitivity among individuals with symptoms > 7 days, but this was limited to a very small pool of samples (N=15). All studies, including ours, found decreases in Panbio sensitivity among SARS-CoV-2 samples with higher Ct values, with sensitivity dropping when Ct values are approximately > 26.…”
Section: Resultsmentioning
confidence: 54%
See 4 more Smart Citations
“…3 Of the studies that examined positivity rate based on symptom duration, one study found no difference in positivity rate with duration of symptom onset 3 , whereas another found higher sensitivity in individuals with symptom onset < 7 days (sensitivity 86.5%) compared to individuals with symptom onset ≥ 7 days (sensitivity 53.8%). 4 We found no difference in Panbio sensitivity among individuals with symptoms > 7 days, but this was limited to a very small pool of samples (N=15). All studies, including ours, found decreases in Panbio sensitivity among SARS-CoV-2 samples with higher Ct values, with sensitivity dropping when Ct values are approximately > 26.…”
Section: Resultsmentioning
confidence: 54%
“…There were false negatives on the Panbio, with 14/17 (82.4%) having a Ct > by RT-PCR and 9/17 (52.9%) with Ct > 30 on RT been identified by the Panbio manufacturer or among previous Panbio publications within the literature. [2][3][4] The PPA of the Panbio varies in the literature from 72.6% to 86.5% among individuals with symptoms ≤ 7 days. [2][3][4] These studies varied in terms of their study design and reference standards used.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations